KARAKTERISASI SPESIFIK DAN NON SPESIFIK EKSTRAK ETANOL DAUN PUTAT (Planchonia valida) - Risa Supriningrum; Nurul Fatimah; Yenni Eka Purwanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Putat plant (Planchonia valida) is a medicinal plant that grows in Mahulu, East Kalimantan. Empirically putat leaves are used to treat skin diseases and reduce black spots on the face. Characterization is the initial stage to determine the quality of an extract. Non-experimental research was conducted to determine the specific and non-specific characteristics of putat plants. Samples in the form of putat shoots were obtained from Mahulu Long Melaham Village, Long Bagun District, Mahakam Ulu Regency, East Kalimantan. The stages of the research include plant determination, sample collection, processing of simplicia, extraction using maceration methods, specific and non specific extracts characterization. Specific characteristics of putat leaf extract include organoleptic test in the form of thick extract, blackish brown color, characteristic odor, bitter taste, average water soluble extract content of 62.50% and ethanol soluble extract 48.75%. Secondary metabolites of putat leaf ethanol extract are alkaloids, flavonoids, tannins, saponins, and steroids. The non-specific characteristics of putat leaf extract include average water content of 23.00%, ash content of 6.47% and acid insoluble ash content of 0.06%. Keywords: Planchonia valida, Characterization, Ethanol extract